Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species - Hammer, Michael P.; Allen, Gerald R.; Martin, Keith C.; Adams, Mark; Ebner, Brendan C.; Raadik, Tarmo A.; Unmack, Peter J. (Zootaxa, 2018)
The freshwater melanotaeniid genus Cairnsichthys is endemic to a relatively small area of specialised habitat within the Wet Tropics bioregion of north-eastern Queensland, Australia. It was previously considered as monotypic, including only a single species, C. rhombosomoides (Nichols & Raven, 1928). The recent discovery of an apparently-isolated population in the Daintree rainforest, approximately 120 km north of the known range extent, prompted a detailed investigation of its taxonomic status using a combined lines of evidence approach. We provide compelling evidence from multiple nuclear genetic markers (52 allozyme loci), mitochondrial DNA sequence data (1141 bp cytochrome b) and morphology (examination of a suite of 38 morphometric and meristic characters) that supports north-south splitting of C. rhombosomoides. Accordingly, we describe the northern population as a distinct species, C. bitaeniatus sp. nov., on the basis of 25 specimens, 34.7–65.6 mm SL. The new species differs morphologically primarily by having a more slender and narrow shape, featuring a flatter, straighter predorsal profile and shorter second dorsal fin base; possession of slightly smaller scales, reflected in higher counts of lateral scales and predorsal scales; typically more vertebrae; and colour differences including a more robust, short black stripe across the upper operculum, a pronounced yellow patch on the anteroventral body and usually a more conspicuous second dark stripe on the lower body, with adult males generally having yellowish compared to reddish fins. We also provide a generic diagnosis for Cairnsichthys and a redescription of C. rhombosomoides. Information on the known distribution, habitats and conservation status of species in the genus is summarised, the new species being of particular concern as a narrow range endemic with specific environmental requirements.